Treatment of posthepatitic cirrhosis by Fuzheng Huayu Tablet (扶正化瘀片) for reinforcing qi and resolving stasis - Deng, Xin; Liang, Jian; Liu, Zhen-wei; Wu, Fa-sheng; Li, Xuan (Chinese journal of integrative medicine, 2013)
Objective To investigate the efficacy and safety of the Fuzheng Huayu Tablet (扶正化瘀片, FZHYT), which is used to reinforce qi and resolve stasis in patients with posthepatitic cirrhosis (PHC). Methods A multicenter, randomized, controlled clinical trial was conducted in 180 patients with PHC. The patients were randomly assigned using random numbers to a treatment group treated with FZHYT and a placebo group; the treatment course was 6 months for both groups. Overall response, adverse events (AEs), and the 2-year survival rate were assessed after treatment. Evaluations were made on changes in liver function, liver fibrosis, coagulation, hemodynamics, degrees of esophagogastric varices, ascites, quality of life (QOL), and scores of main symptoms. Results The overall response was significantly higher in the treatment group than the placebo group (86.7% vs. 62.2%, P <0.01). Patients in both groups had significant improvements in liver function [total bilirubin (TBIL), albumin (ALB)], liver fibrosis [hyaluronic acid (HA), type IV collagen (CIV)], coagulation [prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen (FIB), and thrombin time (TT)], hemodynamics portal venous flow (PVF), and splenic vein flow (SVF) after treatment. Between-group comparisons showed that compared with the placebo group patients in the treatment group achieved significantly greater improvements in TBIL, ALB, HA, C IV, PT, APTT, PVF, SVF, time to ascites resolution, 2-year survival, QOL, and symptom scores ( P <0.05 or P <0.01). There were no significant AEs during the treatment. Conclusion FZHYT is effective and safe for the treatment of hepatic cirrhosis as it is associated with improved liver function, liver fibrosis, coagulation, portal hypertension state, QOL, 2-year survival rate, and fewer AEs.